Optical coherence tomography angiography study on retinochoroidal thickness and blood flow changes after posterior scleral reinforcement surgery - Yongqi Mao; Hao Chen; Yunhua Tang; Haoming Geng; Fuwen Zhang (Photodiagnosis and Photodynamic Therapy)
Purpose: Based on optical coherence tomography angiography (OCTA), we investigate the effects of posterior scleral reinforcement surgery on the fundus structure and function in patients with high myopia. Methods: Retrospective clinical study. Forty cases (41eyes) of high myopia patients who underwent posterior scleral reinforcement surgery at Chengdu University of Traditional Chinese Medicine Affiliated Silver Eye Hospital from January 2022 to January 2025 were selected. Follow-up periods included postoperative 3 months, 6 months, and 1 year. Key indicators before and after surgery were compared, including best-corrected visual acuity (BCVA), axial length (AL), spherical equivalent (SE), retinal thickness (RT), choroidal thickness (CT), and Superficial retinal capillary plexus density (SCP), deep retinal capillary plexus density (DCP), choroidal vascularity index (CVI), choroidal stromal vascularity index (CSI). Results: The study included 40 patients (41 eyes), comprising 9 male patients (9 eyes) and 31 female patients (32 eyes), with a mean age of 42.05 ± 18.71 years.At the last follow-up, patients showed significantly shortened AL (P < 0.001), significantly improved BCVA (P < 0.05), and significantly increased CT (P < 0.05).SCP also exhibited significant postoperative increases (P < 0.05). Additionally,CVI and CSI showed significant postoperative elevation (P < 0.05). Conclusion: This study demonstrates that posterior scleral reinforcement achieves axial stabilization through mechanical reinforcement, mitigates vitreous traction forces on the retina and choroid, enhances visual acuity, improves choroidoretinal microcirculation, and optimizes fundus architecture.